The economic crisis and it's impact on household income and expenditures perspectives from women-headed households in Tacloban city - Cular, Anita G. (Iloilo City UP Visayas, 2006)
"This paper presents the perception of the female household heads in Tacloban City on the impact of economic crisis on their household income and expenditures. With thirty women as survey respondents, all agreed that the economic crisis is still prevalent. However, the degree of the impact varied. Majority of the women claimed that their expenditures on basic necessities were affected by the crisis. On expenditures on non-essential goods and services, almost three quarters of the women reported not being affected by the crisis. When it comes to expenditures on celebrations, the results indicated that majority were not affected. Worth emphasizing was the finding that across the various expenditures, savings was the most severely affected by the crisis. In general, the impact of the crisis on their income and expenditures showed that majority of them was moderately affected. The data also supported the consumption function, which stipulates that when income decreases due to economic crisis, consumption expenditures also decrease."
Keywords: Economic conditions -- Women; Tacloban City -- Economic conditions